The tin men : a novel - DeMille, Nelson; DeMille, Alex (DeMille, Nelson. Scott Brodie & Maggie Taylor series, 2025)
"At a top-secret Army training facility in the Mojave Desert, Special Agents Scott Brodie and Maggie Taylor plunge into a deadly web of military suspense, AI technology, and robot soldiers as they unravel the shocking murder of a senior scientist in this gripping thriller from New York Times bestselling authors Nelson DeMille and Alex DeMille. Army CID Special Agents Scott Brodie and Maggie Taylor team up for their toughest assignment yet as they are dispatched to Camp Hayden to investigate the death of Major Roger Ames, the chief scientist in charge of the top-secret war games being conducted between a platoon of Army Rangers and a fleet of "lethal autonomous weapons." Brodie and Taylor find themselves at ground zero of the next generation of warfare, and must untangle the complex web of alliances, animosities, and secret agendas among the men and women of the isolated facility. In a place cut off from the world and exposed to the harsh desert elements, everyone is a suspect-from the zealous camp commander who pushes his men to the limit, to the Rangers slipping into madness due to isolation, grueling training, and rampant abuse of performance-enhancing drugs, to the late Major Ames's own research colleagues. Brodie and Taylor must uncover layers of deception to find the hidden hand behind the murder of Major Ames, and the real purpose of the activities at Camp Hayden and its terrifying arsenal of next-generation weapons. This gripping thriller, the final novel from the legendary Nelson DeMille, coauthored with his son Alex DeMille, is a masterful blend of suspense and cutting-edge technology. It is a page-turning and thought-provoking exploration of the implications of AI in modern warfare and is a must-read for fans of military thrillers"-- Provided by publisher.